Burya A.I., Tomina A.-M.V., Chernov V.A. Effect of fiber on oksalon tribological characteristics organic plas-tics based on phenylone С–1. - Буря, А.И.; Томина, А.-М.В.; Чернов, В.А. (Problems of Tribology, 2016)
An important role in terms of improving the reliability of mobile joints and machinery is the development of new anti-friction materials, especially organic plastics. Organic plastics different from the typical representatives composition ma-terials polymeric nature of the two components of the polymer - fiber and matrix. Organic plastics filled with fibers of flexible chain polymers, are materials in which the most advantageous proper-ties of these fibers are used (high dielectric and thermal properties, chemical resistance, tribological characteristics) The ef-fect of the content of the heat-resistant fiber oksalon on the tribological characteristics of organic plastics on the basis of aro-matic phenylone C-1. Tests have shown that with the increase of fiber content in organoplastics coefficient of friction and wear are dramatically reduced. It is found that the obtained composites to achieve reduced wear of 3.8 - 12.1 times the coeffi-cient of friction by 49 - 56%, respectively, and the track depth decrease abrasion surface compared to the starting polymer. Polymer composites based on phenylone are among the most promising polymer materials, which together with high levels of physical - mechanical and thermal properties have a high resistance to wear by friction in a pair with the steel. The filler used polyoxadiazole fiber oksalon. Selection of the filler was determined on the one hand, its strength and antifriction properties, and on the other - a chemical affinity to the polymer matrix. For polyoxadiazole fibers are used as monomers phthalic acid and hydrazine, and the solvent - sulfuric acid and oleum available and cheap mass production prod-ucts. Keywords: phenylone C-1, an organic fiber oksalon, coefficient of friction, wear hardness.